Dissolving binding theory - Rooryck, Johan; Wyngaerd, Guido J. vanden, 1964- (Oxford : Oxford University Press, 2011)
This book examines the distribution of anaphors and pronouns. Through a detailed analysis of simplex and complex anaphors in Dutch and English, as well as other Romance and Germanic languages, the authors show that the relationship between an anaphor and its antecedent can be captured in terms of general Minimalist principles.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Anaphora (Linguistics)